Education and the COVID-19 pandemic: implications for teaching practices and identities in a Colombian teacher training college - Orozco Gómez, William (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2022)
Objective: recognize implications of covid-19 pandemic in teachers’ identities and practices in a Colombian Normal Higher School during the period March 2020 - March 2021. Originality/Contribution: the interest for understanding a global phenomenon that particularly affects teachers due to home schooling. Method: hermeneutical paradigm and mixed approach are part of methodology that operates from grounded theory method. Strategies/information collection: For this case, data were collected from techniques such as surveys, focus group, and semi-structured interviews. This information was analyzed to open, axial, and selective coding until theoretical saturation of emerging categories and developing of substantive theory. Conclusions: it was possible to notice the recognition of four great tensions that teachers have experienced during the pandemic and that have fissures in their ways of being, doing and thinking. Similarly, other avatars were observed in teachers’ responses to challenges and finally it was perceived a metamorphosis process of practices and identities, which act interdependently.